Uma abordagem para desenvolvimento de linhas de produtos de software orientada a características e dirigida por modelos - Pereira, Rodrigo Reis (2010)
Software Product Lines are an emerging paradigm for software development, based on systematic reuse of modular assets, enhancing the perspectives of eciency and productivity of businesses. The main focuses of this approach are: increasing product quality, scalability, reduced delivery times, reduced costs of production and maintenance, in addition to mass customization. The model aims to expand the eciency and eectiveness of the development process, exploring the similarities and controlling the variability of member products of a family. The Feature Oriented Model Driven Development (FOMDD) is a blend of FOP (Feature Oriented Programming) and MDD (Model Driven Development). MDD uses models to specify programs and model transformations to synthesize executables. FOP is a paradigm for product lines in which software programs are built from the composition of features. FOMDD proposes the construction of products of a software product line by creating models composed of features and by their transformation into executables. This work is a proposal for a generalization of the FOMDD method presented by Trujillo and others, where the specication of application domains is done with high level models, whose elements are annotated with features, allowing the selection of specic elements for product conguration. This work shows how a set of analysis models can be transformed into platform independent architectural specications, and these in source code, using transformations which introduce technology specic details, allowing the generation of concrete specications for products in dierent technologies, from the same architectural design. Our work shows how models not explicitly fragmented in terms of features can be used as input for the generation of feature oriented code artifacts, allowing the use of legacy models in a feature oriented and model-driven development process. For the evaluation of the approach we present a case study for the generation of interactive systems, specied according to the MVC architectural pattern. This generation is based on a transformation framework that consists on the denition of analysis and design models, on the denition of code specication format, as well the denition and implementation of processing procedures that allow obtaining the nal product.